Penggabungan Sifat Binary Min Heap dan Max Heap pada Struktur Data Min-Max Heap dan Max-Min Heap: Konsep dan Visualisasi - Edison Pardengganan Siahaan (Jurnal Riset Multidisiplin Edukasi, 2026)
This paper outlines the organizational mechanisms of two variants of the Binary Heap data structure, namely the Binary Min-Max Heap and the Binary Max-Min Heap. These variants are derived from a combination of characteristics found in the Binary Min Heap and Binary Max Heap, allowing users to efficiently retrieve both minimum and maximum values from a collection of stored and organized data. In addition to discussing the conceptual and operational aspects of these structures, the paper also presents the design of a software tool developed to visualize the organization process, particularly the procedures for inserting new nodes and deleting existing nodes from the data structures. The visualization is represented through a class diagram, which illustrates the internal structure of the program, including the attributes and methods involved in its implementation. This design aims to assist users in gaining a more intuitive understanding of the internal workings of both Binary Heap variants.